Public faces, secret lives : a queer history of the women's suffrage movement - Rouse, Wendy L. (New York University Press, 2022)
"Over one hundred years ago, women organized to fight for a federal suffrage amendment. But many suffragists were fighting for much more than the vote. The suffrage movement included individuals who represented a wide range of genders and sexualities. It also included a variety of queer relationships. But, suffrage leaders concerned with presenting a respectable public image concealed the queerness of the suffrage movement. This resulted in greater policing of suffragist behavior as suffrage leaders, many of them queer themselves, publicly conformed to gendered views of acceptable appearance and behavior. The problematic effect was to erase the queer history of the movement. Instead suffrage leaders reinforced a patriarchal, heteronormative, cisgender standard of ideal femininity in order to make suffragists and women's suffrage more palatable to the public. The legacy of queer suffragists, however, could not be so easily erased. This book explores how queer women led the suffrage movement while challenging heteronormative concepts of domesticity, family, space, and death in both subtly subversive and radically transformative ways. This book also highlights the alliances that queer suffragists built and the innovative strategies they developed to protect and preserve their most intimate relationships - relationships that were ultimately crucial to the success of the suffrage movement"--